2014
DOI: 10.1186/s12989-014-0063-3
|View full text |Cite
|
Sign up to set email alerts
|

Titanium dioxide nanoparticles promote arrhythmias via a direct interaction with rat cardiac tissue

Abstract: BackgroundIn light of recent developments in nanotechnologies, interest is growing to better comprehend the interaction of nanoparticles with body tissues, in particular within the cardiovascular system. Attention has recently focused on the link between environmental pollution and cardiovascular diseases. Nanoparticles <50 nm in size are known to pass the alveolar–pulmonary barrier, enter into bloodstream and induce inflammation, but the direct pathogenic mechanisms still need to be evaluated. We thus focused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 44 publications
(50 reference statements)
4
63
0
2
Order By: Relevance
“…9,13,23 There are two main mechanisms to explain how pulmonary NPs exposure can initiate cardiovascular responses. One hypothesis states that NPs deposited in the lung elicit local inflammatory responses via oxidative stress that further develop into systemic oxidative stress/inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,13,23 There are two main mechanisms to explain how pulmonary NPs exposure can initiate cardiovascular responses. One hypothesis states that NPs deposited in the lung elicit local inflammatory responses via oxidative stress that further develop into systemic oxidative stress/inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…12 A recent animal study has shown that a single intratracheal administration of saline solution containing TiO 2 nanoparticles increases cardiac conduction velocity and tissue excitability, resulting in an enhanced propensity for inducible arrhythmias. 13 In addition, both multiwalled carbon nanotubes and ZnO-NPs have been demonstrated to induce procoagulant effects.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this, some respiratory toxicity studies have shown that TiO 2 NPs indeed can affect the cardiovascular system. Savi et al (2014) found that in vivo a single intra-tracheal administration of saline solution containing TiO 2 NPs at dose of 2 mg/kg increased cardiac conduction velocity and tissue excitability on healthy rats, resulting in an enhanced propensity for inducible arrhythmias). Kan et al (2014) demonstrated that pulmonary inhalation of ultrafine titanium dioxide (UF TiO 2 ) significantly increased heart rate and elevated mean and diastolic blood pressure in response to norepinephrine (Kan et al, 2014).…”
Section: Tablementioning
confidence: 96%
“…Similar kind of result was found by [20] synthesizing the zinc oxide nanoparticles by micro emulsion method. From the UV-visible spectrometer analysis concluded that zinc oxide and iron oxide nanoparticles had an intense absorbance at ∼250 nm which indicates that the synthesized particles were photosensitive in UV region [21].…”
Section: Uv-visiblementioning
confidence: 99%